GAMBARAN PERILAKU SEXTING PADA REMAJA DI SMK PARIWISATA X BADUNG - Komang Anisa Anggun Cahyaningrum; I Gusti Ayu Pramitaresthi; Meril Valentine Manangkot (Coping: Community of Publishing in Nursing, 2021)
Adolescence takes place at the age of 10-19 years which is the stage towards adulthood. Puberty phase which occurs in the early stage of teen age, causes them change. One of them is sexual development. Teenagers can channel their sexual desires through sexual behavior. Indirect sexual behavior can be done through sexting. Sexting can cause some negative effects for teens such as triggering risky sexual activity, cybercrime, and psychological pressure. The aims of this study is to determine the characteristics of adolescents and the characteristics of sexting behavior using a descriptive method. This study involved 154 adolescents aged 15-16 years at SMK Pariwisata X Badung. The measuring instrument used was the Sexting Behaviors Questionnaire. Based on the result of the study, from 154 respondents, there are 112 respondents were classified into low sexting behavior. Based on the frequency of engaging in sexting activities, there are 114 respondents never received sexual photos or videos of the people they knew, then 148 of them never sent sexual photos or videos, and as many as 104 respondents did not respond to the sexual content which they received. Based on this data, although the majority of respondents answered never in one aspect of the question, but some respondents said they had sexed in accordance with questionnaire question items. This show that some teenagers are involved in sexting activities. The results of this study can be used as basic data in conducting further research related to sexting behavior.